Impact of Loan Defaults on the Profitability of Nepalese Commercial Banks - Ranjitkar, Abiral; Tamrakar, Ashna; Upreti, Ajit; Silwal, Abin; Basnet, Amar; Pradhan, Radhe Shyam (Nepalese Journal of Finance, 2024)
The study examines the effect of loan defaults on the profitability in Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are bank size, interest spread rate, loan loss provision, non-performing loan, capital adequacy ratio, and credit to deposit ratio. The study is based on secondary data from 17 commercial banks with 102 observations for the study period from 2016/17 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of loan defaults and other bank specific factors on the profitability of selected Nepalese commercial banks. This study showed that nonperforming loan has a negative impact on return on assets and return on equity. It means that increase in that nonperforming loans leads to decrease in return on assets and return on equity. In addition, loan loss provision has a negative impact on return on assets and return on equity. It means that increase in loan loss provision leads to decrease in return on assets and return on equity. Likewise, capital adequacy ratio has a positive impact on return on assets. It shows that higher the capital adequacy ratio, higher would be the return on assets. In contrast, capital adequacy ratio has a negative impact on return on equity. Moreover, credit to deposit ratio has a positive impact on return on assets. It indicates that increase in credit to deposit ratio leads to increase in return on assets. In addition, interest spread rate has a positive impact on return on assets. It indicates that increase in interest spread rate leads to increase in return on assets. Similarly, there is a positive relationship between bank size has a positive impact on return on equity. It means that larger the bank size, higher would be the return on equity.